Relationships between higher‐level functional capacity and dental health behaviors in community‐dwelling older adults. (19th April 2012) - Moriya, Shingo; Tei, Kanchu; Yamazaki, Yutaka; Hata, Hironobu; Kitagawa, Yoshimasa; Inoue, Nobuo; Miura, Hiroko
<x xml:space="preserve">Abstract</x> doi: 10.1111/j.1741‐2358.2012.00654.x Relationships between higher‐level functional capacity and dental health behaviors in community‐dwelling older adults Objective: The aim of the present study was to elucidate relationships between higher‐level functional capacity and dental health behaviours in community‐dwelling older adults. Background: In ageing society, it is necessary to promote oral health in the elderly, because good oral health is a significant contributing factor to good general health. Higher‐level functional capacity has been considered a crucial factor for successful independent living in the elderly. We hypothesised that functional capacity is a significant indicator of dental health behaviours. Methods: Three hundred and thirty‐eight adults aged 65 years or older were enrolled in this study. Higher‐level functional capacity was evaluated using the Tokyo Metropolitan Institute of Gerontology Index of Competence (TMIG‐index). Univariate and multivariate models were constructed with dental health behaviours, such as regular visits to a dentist, brushing frequency and use of extra cleaning devices, as the dependent variable, and the total TMIG‐index score and its subcategory scores as the principal independent variable. Results: Univariate logistic regression analysis demonstrated a significant correlation between low TMIG‐index and 'intellectual activity' subcategory scores to lack of regular visits to a dentist and not using extra cleaning devices. Using a multivariate model, significant relationships remained after adjusting for a number of variables including demographics, medical status, lifestyle and number of remaining teeth. Conclusion: Intellectual activity of higher‐level functional capacity may be an accurate indicator of dental health behaviours in community‐dwelling older adults. Intellectual activity should be taken into consideration to effectively promote oral health behaviours and oral hygiene in elderly persons living independently.